« PROBLEMATIQUE DE LA GESTION DE LA FAUNE SAUVAGE DANS LE DOMAINE DE CHASSE DE RUBI-TELE FACE A LA PRESSION DE LA POPULATION LOCALE (Province de Bas-Uélé, RD Congo). » - Marc, BOKETSHU ILONGA; Elysée, KASONGO WALO; Crispin, GEMBU TUNGALUNA Guy (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2021)
ABSTACT In the present study we analyze and report on location of wildlife population in the Rubi-tele hunting area in the Bas-Uele province in the Democratic Republic of Congo. This reserve is under due to illicit synergistic activities. The results of our study show that the hunting area of Rubi-tele is a protected area with protection statut, local. Also this reserve abound in important animals resource, but wich is serously exploited and leads to the removal of these species.